2018
DOI: 10.1111/jmwh.12729
|View full text |Cite
|
Sign up to set email alerts
|

Yoga and Quality of Life in Women with Primary Dysmenorrhea: A Systematic Review

Abstract: Practitioners may consider yoga for management of primary dysmenorrhea. However, future research using larger RCTs of high methodological quality is needed to ascertain the magnitude of yoga's clinical significance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
40
0
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(41 citation statements)
references
References 41 publications
0
40
0
1
Order By: Relevance
“…In the last decade, several authors have noted the need to further study both the pharmacological and non-pharmacological management of menstrual pain [ 10 , 11 , 35 ], especially considering that 18% of non-steroidal anti-inflammatory treatments are ineffective for dysmenorrhea, the primary treatment for this condition [ 36 ]. There is increasing evidence of the efficacy of non-pharmacological methods for dysmenorrhea, such as aerobic exercise, yoga, taping and transcutaneous electrical nerve stimulation [ 20 , 21 , 37 , 38 , 39 ]. Furthermore, a study conducted in the USA among women suffering from dysmenorrhea identified the reasons why women did not seek medical advice: they believed professionals would be unable to help, they distrusted the available treatments and felt ashamed or fearful of seeking help for this problem [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the last decade, several authors have noted the need to further study both the pharmacological and non-pharmacological management of menstrual pain [ 10 , 11 , 35 ], especially considering that 18% of non-steroidal anti-inflammatory treatments are ineffective for dysmenorrhea, the primary treatment for this condition [ 36 ]. There is increasing evidence of the efficacy of non-pharmacological methods for dysmenorrhea, such as aerobic exercise, yoga, taping and transcutaneous electrical nerve stimulation [ 20 , 21 , 37 , 38 , 39 ]. Furthermore, a study conducted in the USA among women suffering from dysmenorrhea identified the reasons why women did not seek medical advice: they believed professionals would be unable to help, they distrusted the available treatments and felt ashamed or fearful of seeking help for this problem [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although recent systematic reviews and meta-analyses have assessed the efficacy and safety of yoga in specific groups of women, such as those with prenatal depression [19] and primary dysmenorrhea [20] in different stages, evidence for the efficacy of yoga in improving sleep quality and insomnia of women has not yet been systematically assessed. Thus, the aim of this review was to systematically evaluate and perform a meta-analysis of the available data on the efficacy and safety of yoga in terms of improving sleep quality and insomnia in women.…”
Section: Introductionmentioning
confidence: 99%
“…Although recent systematic reviews and meta-analyses have assessed the efficacy and safety of yoga in specific groups of women, such as those with prenatal depression [20] and primary dysmenorrhea [21] in different stages, evidence for the efficacy of yoga in improving sleep quality and insomnia of women has not yet been systematically assessed. Thus, the aim of this review was to systematically evaluate and perform a meta-analysis of the available data on the efficacy and safety of yoga in terms of improving sleep quality and insomnia in women.…”
Section: Introductionmentioning
confidence: 99%